Eradicating women-hurting customs: What role for social engineering? - Jean-Philippe Platteau; Guilia Camilotti; Emmanuelle Auriol (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Social engineering refers to deliberate attempts, often under the form of legislative moves, to promote changes in customs and norms that hurt the interests of marginalized population groups. This paper explores the analytical conditions under which social engineering is more or less likely to succeed than more indirect approaches when it comes to suppress genderbiased customs. This implies discussing the main possible interaction frameworks leading to antiwomen equilibria, and deriving policy implications from the corresponding games. The theoretical arguments are illustrated by examples drawn from available empirical works, thus providing a reasoned survey of the literature.
Keywords: D10; K10; K36; O15; Z10; Z13; 330; social norms; harmful customs; gender; coordination incentives; expressive function of law; deterrence; Frauenpolitik; Sozialtechnologie; Geschlechterdiskriminierung; Soziale Werte; Familienrecht; Rechtsökonomik; Spieltheorie; Theorie; Entwicklungsländer